EXAMINATION AND TESTING OF EXPERIMENTAL-PRODUCTION SERIES OF POLYVALENT BRUCELLOSIS SERUM - N. M. Andreevskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
At present no commercial polyvalent brucellosis serum is produced in Russia. We developed a technology of polyvalent brucellosis high-effective and specific serum production without adsorption. Experimental-production series are obeyed the technical specification project.